Therapeutic Potential of an Azithromycin-Colistin Combination against XDR K. pneumoniae in a 3D Collagen-Based In Vitro Wound Model of a Biofilm Infection - Olena V. Moshynets; Taras P. Baranovskyi; Olga S. Iungin; Alexey A. Krikunov; Viktoria V. Potochilova; Kateryna L. Rudnieva; Geert Potters; Ianina Pokholenko (MDPI AG, 2023)
A therapeutic combination of azithromycin (AZM) and colistin methanesulfonate (CMS) was shown to be effective against both non-PDR and PDR Klebsiella pneumoniae biofilms in vitro. These anti-biofilm effects, however, may not correlate with effects observed in standard plate assays, nor will they representative of in vivo therapeutic action. After all, biofilm-associated infection processes are also impacted by the presence of wound bed components, such as host cells or wound fluids, which can all affect the antibiotic effectiveness. Therefore, an in vitro wound model of biofilm infection which partially mimics the complex microenvironment of infected wounds was developed to investigate the therapeutic potential of an AZM-CMS combination against XDR K. pneumoniae isolates. The model consists of a 3D collagen sponge-like scaffold seeded with HEK293 cells submerged in a fluid milieu mimicking the wound bed exudate. Media that were tested were all based on different strengths of Dulbecco's modified Eagles/high glucose medium supplemented with fetal bovine serum, and/or Bacto Proteose peptone. Use of this model confirmed AZM to be a highly effective antibiofilm component, when applied alone or in combination with CMS, whereas CMS alone had little antibacterial effectiveness or even stimulated biofilm development. The wound model proposed here proves therefore, to be an effective aid in the study of drug combinations under realistic conditions.